A Study on the Behaviour of 15 Storeys 2x3bay with Soil Flexibility - S, Deepa; S V, Venkatesh; R.Mithanthaya, I (International Journal of Engineering and Technology, 2018)
Previous analytical study was precisely based on structures with rigid base and soil conditions where neglected which showed considerable difference in the behaviour of structures. The present study is mainly based on flexible base considering soil effect with raft foundation. The structure considered is in seismic zone 5 with different types of soil condition such as hard soil, medium soil and soft soil. Also the structural irregularity is compared such as regular structure, structure with horizontal irregularity and structure with vertical irregularity. The soil is idealised by Modified Winkler method and Continuum method with Raft foundation. Overall 9 models where analysed in each method. The results are compared between Modified Winkler method and Continuum method with regular, horizontal and vertical irregularities for all 3 types of soil (Hard soil, Medium soil and Soft soil). Results where compared for Base shear, Axial forces, Time period and Displacement which shows that Continuum method of SSI gives realistic results compared to Modified Winkler method.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â